2015
DOI: 10.1016/j.jff.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous release of peptides and phenolics with antioxidant, ACE-inhibitory and anti-inflammatory activities from pinto bean (Phaseolus vulgaris L. var. pinto) proteins by subtilisins

Abstract: Available online A B S T R A C TProduction of novel functional ingredients from legume proteins is a valuable strategy to boost their food use and intake. Aimed at a better exploitation of the functional properties of pinto bean hydrolysates, the effectiveness of two subtilisins (Alcalase and Savinase) for the simultaneous release of bioactive peptides and phenolics with antioxidant, angiotensin I converting enzyme (ACE) inhibitory and anti-inflammatory activities was investigated.A higher proteolytic efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 48 publications
8
55
3
2
Order By: Relevance
“…Soaking of whole seeds was not performed in this study as it was in the aforementioned studies; however, PPEF was dispersed in water and left to stir overnight as a form of solubilization and then heated at 80°C in a water bath for 30 min during the enzymatic treatments which may have contributed to the lack of increase in total phenolics content of the enzyme‐treated PPEF. Garcia‐Mora et al () determined that using Savinase and Alcalase could better release total phenolic compounds from pinto beans than soaking alone, as Alcalase doubled the total phenolic content after 120 min of hydrolysis, and Savinase‐treated pinto beans had 2.5 times higher phenolic content after 120 min of hydrolysis. This could be expected in peas; however, after hydrolysis and centrifugation in the present study, the supernatant was removed; thus, any solubilized phenolic compounds that were released due to enzymatic modification would have been discarded with the supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…Soaking of whole seeds was not performed in this study as it was in the aforementioned studies; however, PPEF was dispersed in water and left to stir overnight as a form of solubilization and then heated at 80°C in a water bath for 30 min during the enzymatic treatments which may have contributed to the lack of increase in total phenolics content of the enzyme‐treated PPEF. Garcia‐Mora et al () determined that using Savinase and Alcalase could better release total phenolic compounds from pinto beans than soaking alone, as Alcalase doubled the total phenolic content after 120 min of hydrolysis, and Savinase‐treated pinto beans had 2.5 times higher phenolic content after 120 min of hydrolysis. This could be expected in peas; however, after hydrolysis and centrifugation in the present study, the supernatant was removed; thus, any solubilized phenolic compounds that were released due to enzymatic modification would have been discarded with the supernatant.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their therapeutic quality, bioactive peptides should possess specific functional properties to facilitate processing. In the same context, Garcia-Mora et al [20] investigated the effectiveness of Alcalase R and Savinase R for the simultaneous release of bioactive peptides and phenolics with antioxidant, angiotensin I converting enzyme (ACE) inhibitory and anti-inflammatory activities. In fact, the controlled enzymatic hydrolysis of protein produces smaller polypeptides that modify and even enhance functional characteristics for a wide range of applications [18].…”
Section: Preparation and Characterization Of Shrimp Waste Protein Hydmentioning
confidence: 99%
“…(Yu et al 2016). Previous studies have revealed the active components are associated with various beneficial activities, including antioxidant, immunomodulatory (Garcia-Mora et al 2015), anticancer (Chan et al 2016) and other biological effects. There are many species of legumes such as soybean (Yu et al 2016), pinto bean (Garcia-Mora et al 2015), and kidney bean (Shevkani et al 2015), etc.…”
Section: Introductionmentioning
confidence: 99%